Lecithin decorated thin film composite (TFC) nanofiltration membranes for enhanced sieving performance - Cheng, Lilantian (2023)
Lecithin, as a natural bio-surfactant and environment-friendly bio-modifier, has been broadly applied in food, cosmetic, and pharmaceutical industries. At present, the application of lecithin materials is mainly on constructed liposomes that provide a recombination platform for aquaporins to prepare biomimetic membranes. Only few studies directly use lecithin as additives or surface activators to modify nanofiltration (NF) membrane. Herein, soybean lecithin (SL) was applied as an additive of aqueous phase to tune the interfacial polymerization (IP) process to achieve thin-film composite (TFC) NF membrane with enhanced perm-selectivity for dye/salt separation. The structures and properties of the membranes were investigated by varying the SL concentrations in aqueous phase solution. The results revealed that SL incorporated NF membranes possessed a thinner selective layer and rougher surface morphology, which guaranteed a higher water permeance. At optimal conditions with 0.05 wt % SL decoration, TFC membrane displayed a high pure water permeance to 43.8 L m−2 h−1 bar−1 with over 99.0% dye rejections towards Congo red (MW: 696.7 Da), Xylene brilliant cyanin G (MW: 854.0 Da), Reactive blue 19 (MW: 626.5 Da) and Methyl blue (MW: 799.8 Da). Moreover, the SL decorated membrane maintained low chloride salts rejections (17.5% for NaCl, 7.2% for MgCl2) and satisfying sieving ability when filtrating dye/salt mixture solution. These results surpassed most of the published data, implying their unprecedented potential for desalination application.